Pelatihan ECO - Riding Pada Pelajar Sekolah Menengah Kejuruan (SMK) Untuk Mengurangi Konsumsi Bahan Bakar dan Resiko Kecelakaan - Widiyatmoko Widiyatmoko; Arif Susanto; Mike Elly Anitasari; Muhammad Abdul Wakhid (Lembaga Pengembangan Kinerja Dosen, 2024)
Eco Riding is an environmentally friendly driving technique that is oriented towards fuel efficiency. Eco Riding Driving is a relatively cheap measure to significantly reduce fuel consumption and emissions. Eco Riding is a driving behavior that can extend the service life of a vehicle and reduce the potential or risk of accidents. The aim of Eco driving is to increase motorists' awareness of environmentally friendly, safe and comfortable driving techniques. The stages of implementing this activity include: 1) Analysis of program needs, 2) Activity planning, such as coordination with partners, determining the place and time for implementation, 3) Implementation of activities with presentation of Eco driving material. Based on the results of implementing community service activities, it can be stated that community service activities can be carried out well. From the evaluation results of the implementation of the ECO riding training service, it was found that the average implementation of the activity was 92.25 percent. Thus, it can be concluded that the implementation of community service, namely that vocational school students have been able to carry out well in accordance with the goals of service